Intraprenuers - Jordan, Peter; Katten, Steve (Del Mar, Calif. : Mcgraw-Hill Training Systems, 1986)
Takes the viewer behind-the-scenes of corporate giants such as DuPont, Digital Equipment Corporation and Polaroid Corporation for first-hand accounts of intrapreneuring. Through interviews with both intrapreneurs themselves and themanagers who supported them by taking financial and political risk, viewers learn how these were brought to fulfillment
Bibliographical information is taken from computer-printout, Bibliofile
Keywords: Risk management; Risk management -- United States -- Interviews